(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The study focused on measuring the impact of the increase and decrease in the scale of bank financing which allocated to the foreign trade sector on the trade balance in Sudan during the period 2000-2022, and by depending on cointegration method, nonlinear autoregressive distributed lagged model(NARDL) and time series data it was concluded that the increasing in bank financing in the long- run leads to an improvement in the trade balance, while the decrease in bank financing does not have anegative effect, and the inbalance in the relationship is corrected by -1.87, and the financing authorities must adopting appropriate financing policies which is work to balance the structure of bank financing and the uses of financial resources directed to the foreign trade sector to correcting the inbalance in trade balance.